Household Food-Related Assessment Using an Innovative Passive Dietary Assessment Device in Ghana. (29th May 2020) - Anderson, Alex; McCrory, Megan; Steiner-Asiedu, Matilda; Ansong, Richard; Lewis, Clara; Ghosh, Tonmoy; Higgins, Janine; Sazonov, Edward
Abstract: Objectives: Traditional dietary assessment methods in low-middle income countries (LMICs) have considerable limitations. the objective of this study was to test the feasibility of using the Automatic Ingestion Monitor (AIM), an eyeglasses-mounted wearable chewing sensor and micro-camera, to monitor food acquisition, preparation and consumption of households in a LMIC setting. Methods: Data from households in Mampong-Akuapem ( n = 5), a semi-rural community, and Kweiman ( n = 7), a peri-urban community, in the Eastern and Greater Accra Regions of Ghana, respectively, were evaluated. The AIM was used to monitor household activities for one day. Within each household, the primary caregiver (mother) wore the AIM during waking hours on the chosen day as she went about her daily activities, except any activities where she wanted to preserve privacy. Mothers also responded to a socio-demographic questionnaire and evaluated their perceived burden of wearing the AIM. Images captured by the AIM were processed and annotated in custom-designed software. Time spent in major household related activities around food are described. Results: Households had 1.9 ± 0.3 adults and 2.8 ± 1.6 children (mean ± SD). Primary caregivers were 30.5 ± 5.2 years of age, all were married (1 separated), and had a median of 9 years of formal education. Two mothers were breastfeeding at data collection, but only 1 household had an infant <1 year. Total AIM wear time was 8 h, 19 min ± 2 h, 11 min, representing 58% of waking hours. All members of each household consumed the same prepared meals, and all meals were captured by the AIM. Among mothers, time spent cooking varied widely (2 h, 19 min ± 1 h, 42 min), ranging from 0.5 to 6 h. Time spent eating and drinking was 41 ± 15 min. Most of the mothers ( n = 10) spent time feeding children (17 ± 23 min, including breastfeeding), with 6 mothers feeding younger children (11 ± 10 min), 5 feeding older children (7 ± 4 min), and 2 breastfeeding (53 ± 25 min). The AIM was generally accepted by the primary caregivers and household members although they would prefer a smaller size version. Conclusions: In this pilot study, the AIM successfully captured household food related activities and practices that are associated with dietary intake and nutritional health in LMIC. Funding Sources: The Bill and Melinda Gates Foundation.